Are Primo Vessels (PVs) on the Surface of Gastrointestine Involved in Regulation of Gastric Motility Induced by Stimulating Acupoints ST36 or CV12?. (4th October 2012) - Wang, Xiaoyu; Shi, Hong; Shang, Hongyan; Su, Yangshuai; Xin, Juanjuan; He, Wei; Jing, Xianghong; Zhu, Bing
Abstract : Previous studies showed primo vessels (PVs), which were referred to as Bonhan ducts (BHDs) and a part of circulatory system by Kim, located in different places of the body. The BHDs system was once considered as the anatomical basis of classical acupuncture meridian but not clearly identified by other investigators. In the present study, we tried to address the relationship between PVs and meridians through detecting the modulation of gastric motility by stimulating the PVs on the surface of stomach or intestine, as well as acupoints Zusanli (ST36) and Zhongwan (CV12). The results showed electric stimulation of the PVs had no effect on the gastric motility. While stimulating CV12 inhibited gastric motility significantly in PVs-intact and PVs-cut rats, there is no significant difference between the inhibition rate of the PVS-intact and the PVS-cut rats. Stimulating at ST36 increased gastric motility significantly in both the PVs-intact and the PVs-cut rats, yet there was no significant difference between the facilitation rate of the both groups. Taken together, the PVs on the surface of stomach or intestine did not mediate the regulation of gastric motility induced by stimulating at the acupoints ST36 or CV12.